PENGELOLAAN VALUE-ADDED ACTIVITIES DAN NON-VALUE-ADDED ACTIVITIES MELALUI ANALISIS MANUFACTURING CYCLE EFFECTIVENESS (MCE) DALAM MENINGKATKAN EFISIENSI PRODUKSI (STUDI KASUS PADA UD. KARYA TUNGGAL SIDOARJO) - WIJAYANTO, ISMED (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this research is to analyze the efficiency number of production process by Manufacturing Cycle Effectiveness (MCE) to reduce or eliminate non-value- added activities and improve value-added activities. This research used qualitative analysis method with case study approach, where the concept development and fact accumulation were done by the researcher without examining the hypothesis. The process of collecting data was done by observation, interview, and literature research. The results of this research show that the activities of UD Karya Tunggal Sidoarjo in producing mold and baking pan are still not ideal. It is shown by the MCE value for the mold is 54% and for the baking pan is 65%. This MCE percentage can be used by Management of UD Karya Tunggal Sidoarjo for reducing and eliminating non-value- added activities and doing the improvement of value-added activities in increasing time efficiency of production.